(untitled) (LEARNing Landscapes, 2009)
This article reports the experience of a teacher and researcher who instituted a problem-posing component in her Grade 2/3 mathematics class with the help of a glove puppet, "Sylvester." The activities, based largely on the intuition of an expert teacher, are substantiated by the literature on problem posing. The authors describe what happened in the classroom and some of the benefits of the strategy. Among the most important of these benefits was what the teacher learned about the children and their understanding of mathematics by listening to what they were saying.